Pengaruh Kepemimpinan Kepala Sekolah, Budaya Organisasi dan Motivasi Kerja Terhadap Kinerja Guru Smk Ma’arif 2 Gombong Kebumen - Setyowati Setyowati (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2020)
This research is based on the problem of unsatisfactory teacher performance. In this regard, this study aims to determine the influence of the principal's leadership, organizational culture, and work motivation on teacher performance at SMK Ma'arif 2 Gombong Kebumen. This research is a quantitative study. The population in this study were all teachers at SMK Ma'arif 2 Gombong Kebumen, and the sample in this study was 40 people. Data collection using questionnaires, and data analysis using simple linear regression analysis techniques and multiple linear regression analysis. This study resulted in the following conclusions. (1) The Principal's Leadership has a fairly positive influence on Teacher Performance at Ma'arif 2 Gombong Kebumen Vocational School, as evidenced by the value of Sig = 0.028 < α = 0.05. The value of the correlation coefficient (r2) = 0.347 or contributes 34.7%. (2) Organizational Culture has a strong positive and significant influence on Teacher Performance at Ma'arif 2 Gombong Kebumen Vocational School, as evidenced by the value of Sig = 0.000 < α = 0.05. The value of the correlation coefficient (r2) = 0.725 or a contribution of 72.5%. (3) Work Motivation has a strong positive and significant influence on Teacher Performance at SMK Ma'arif 2 Gombong, Kebumen, as evidenced by the value of Sig = 0.000 < α = 0.05. The value of the correlation coefficient (r2) = 0.631 or contributes 63.1%. (4) Principal Leadership, School Culture, and Work Motivation Together have a strong, positive and significant influence on Teacher Performance at SMK Ma'arif 2 Gombong Kebumen, as evidenced by the value of Sig = 0.000 < α = 0.05. The value of the correlation coefficient (R2) = 0.787 or a contribution of 78.7%.